Visual ultra-high cycle fatigue internal crack growth rate determination method

By recording the heat dissipation temperature field of metal materials under ultra-high fatigue conditions with infrared cameras, visual monitoring and precise positioning of internal cracks are achieved, and the problem of difficulty in monitoring the internal crack propagation of ultra-high fatigue in the prior art is solved, and data accuracy and structural reliability are improved.

CN119574255AActive Publication Date: 2025-03-07BEIHANG UNIV

Patent Information

Application Number
CN202411793298.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-07
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Under ultra-high cycle fatigue conditions, it is difficult to visually observe and accurately non-destructive flaw detection of cracks inside the material. The existing methods are costly and inefficient, and cannot monitor the dynamic process of crack propagation in real time.

Method used

By utilizing the heat dissipation behavior of local plastic deformation and cracking of metal materials, a high-speed infrared camera is used to record the temperature field generated by energy dissipation, and the precise positioning of fatigue crack initiation points and in-situ monitoring of the crack propagation process, and calculations are made by introducing the expansion time and load cycle frequency to obtain the crack propagation rate.

Benefits of technology

Visual monitoring and precise positioning of internal cracks with ultra-high circumferential fatigue is realized, the crack propagation process can be recorded in detail, the data can be obtained are rich and accurate, and the slight changes in the early stage of crack invasion are detected, which improves the reliability of the structure and reduces safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119574255A_ABST
    Figure CN119574255A_ABST
Patent Text Reader

Abstract

The invention relates to a visual method for measuring the expansion rate of an ultrahigh-cycle fatigue internal crack, and belongs to the technical field of measurement of the expansion rate of the fatigue internal crack. A high-speed infrared camera is used for recording a temperature field generated by energy dissipation so as to visualize the crack propagation process, precise positioning of a fatigue crack initiation point of a metal material and in-situ monitoring of the crack propagation process are realized, and the crack propagation rate is obtained by introducing propagation time and load cycle frequency for calculation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of measuring fatigue internal crack growth rate, and in particular to a visual method for measuring ultra-high cycle fatigue internal crack growth rate. Background Art

[0002] Structures and components in the fields of aerospace, defense, military and automotive industries are often subjected to long-cycle fatigue loads. According to statistics on the failure cases of all parts of jet aircraft, up to 49% of the parts fail due to fatigue during service. For key parts in aircraft engines, such as turbine blades and compressor discs, the fatigue cycle loads they bear far exceed 10 7 The traditional high-cycle fatigue category is based on the standard of 10 cycles, and the U.S. "Engine Structural Integrity Program" stipulated as early as the last century that the service life of components used in aircraft engines must reach 10 9 Weeks or more, these 10 7 ~10 9 It has entered the category of ultra-high cycle fatigue, making reliability research on ultra-long life fatigue very necessary.

[0003] A large number of existing studies have shown that in the ultra-high cycle fatigue stage, the initiation and expansion of cracks are located inside the material, and the initial stage of initiation is only at the micron level, which makes it difficult to conduct visual observations and accurate non-destructive testing. The method of scanning and reconstructing the interior of the material by relying on large scientific equipment such as synchrotron radiation and neutron diffraction is also difficult to carry out in situ, and is costly and inefficient. It cannot be used in engineering and cannot detect the dynamic process of crack expansion. The internal cracks in such long-life service components are difficult to accurately locate and monitor in real time, which greatly reduces the reliability of the structure and may pose a major safety hazard to the service components.

[0004] The ASTM-E647 standard recommends three methods for fatigue crack size measurement, including visual method, compliance method and potential difference method. However, the characteristics of internal crack initiation in ultra-high cycle fatigue make these conventional crack length measurement methods unusable. The inventor team once proposed a method to reversely infer the crack growth rate through fracture notches, which can obtain the internal crack growth rate. However, the fracture notches are only an estimation method based on the post-fracture morphology to reverse the rate. It cannot obtain real-time damage conditions, nor can it detect the expansion behavior of small cracks in the early stage of fatigue damage. Therefore, there is an urgent need for a crack growth rate determination method that is accurate in testing, direct in recording, and convenient in application. Summary of the invention

[0005] In view of the above problems, the present invention proposes a visualized method for determining the internal crack growth rate of ultra-high cycle fatigue, which utilizes the local plastic deformation and cracking thermal dissipation behavior of metal materials, and uses a high-speed infrared camera to record the temperature field generated by energy dissipation to visualize the crack growth process, thereby achieving precise positioning of the fatigue crack initiation point of the metal material and in-situ monitoring of the crack growth process, and obtains the crack growth rate by introducing the expansion time and load cycle frequency for calculation.

[0006] The present invention provides a visual method for determining the internal crack growth rate of ultra-high cycle fatigue, comprising:

[0007] S1. Processing a fatigue specimen to be tested; the fatigue specimen to be tested is a variable-section plate-shaped ultrasonic fatigue specimen;

[0008] Preferably, the shape and size of the fatigue specimen to be tested in step S1 are designed according to the dynamic elastic modulus and density of the fatigue specimen to be tested;

[0009] Exemplarily, the fatigue specimen to be tested is processed by an electric spark wire cutting machine.

[0010] The size of the variable cross-section plate-shaped ultrasonic fatigue specimen in step S1 of the present invention satisfies ultrasonic resonance and facilitates high-precision infrared monitoring of the initiated fatigue cracks;

[0011] Exemplarily, a Ti-6Al-4V alloy prepared by additive manufacturing is selected and placed in a heat treatment furnace for 2 hours at 600° C. to obtain a fatigue specimen to be tested;

[0012] The dynamic elastic modulus of the fatigue specimen to be tested is 96.455 GPa;

[0013] The density of the fatigue specimen to be tested is 4.38 g / cm 3 .

[0014] Exemplarily, the ultrasonic resonance frequency of the ultrasonic fatigue testing machine is 20 kHz;

[0015] S2, performing secondary grinding and coating deposition treatment on the surface of the fatigue specimen to be tested to obtain a treated specimen;

[0016] Preferably, the specific steps of obtaining the processed sample in step S2 include:

[0017] Performing mechanical grinding and electrolytic polishing on the surface of the fatigue specimen to be tested, and depositing a matte coating evenly on the surface of the fatigue specimen to be tested after the treatment, to obtain a treated specimen;

[0018] Furthermore, the infrared emissivity of the matte coating is 0.9 to 1;

[0019] Exemplarily, step S2 performs secondary grinding and coating deposition on the surface of the fatigue specimen to be tested, and the specific steps of obtaining the treated specimen include:

[0020] Step S21, using a CNC grinder to perform a first polishing on the surface of the fatigue specimen to be tested; the roughness of the CNC grinder is Ra<0.4;

[0021] Step S22, using 3000-mesh sandpaper and a diamond polishing agent with a particle size of 0.25 μm to perform a second polishing on the surface of the fatigue specimen to be tested after the first polishing;

[0022] Step S23, placing the fatigue specimen to be tested after the second polishing into an alcohol bath configured with polishing liquid;

[0023] It is understood that the temperature of the alcohol bath is -19--21°C;

[0024] The polishing liquid comprises 5.5-6.5% perchloric acid, 58.5-59.5% methanol and 34.5-35.5% n-butanol;

[0025] Step S24, after the temperature is constant at -19--21°C, connect the cleaned sample to the anode of a DC stabilized power supply, connect the cathode of the DC stabilized power supply to a copper sheet, place them together in a polishing liquid, and put a magnetic rotor that continuously stirs the polishing liquid;

[0026] Step S25, power on for 30 seconds to perform electrolytic polishing. After polishing, wash in pure alcohol and quickly dry to obtain a cleaned sample;

[0027] Step S26: using an atomizing device to deposit a layer of matte water-based paint on the surface of the cleaned sample to obtain a treated sample.

[0028] The complex phase interface formed by multiple resin components of the matte water-based paint in the present invention forms a slightly rough surface with strong diffuse reflection of light after the coating is cured, thereby increasing the emissivity of the sample surface and avoiding the reflection of infrared rays by metal, thereby affecting the monitoring quality.

[0029] S3. Before the fatigue test, the emissivity of the coating deposited on the surface of the treated sample is measured to obtain the coating emissivity;

[0030] Preferably, in step S3, a thermocouple and an infrared camera calibrated by a black body are used to measure the emissivity of the coating deposited on the surface of the treated sample to obtain the emissivity of the coating.

[0031] For example, the treated sample is placed in an induction coil, a k-type thermocouple is selected for temperature measurement, and the thermocouple is fixed on the surface of the sample using a spot welder under a welding current of 60A;

[0032] At the same time, a high-precision infrared camera calibrated by a black body is selected for synchronous temperature measurement.

[0033] Furthermore, when the temperature measured by the thermocouple reaches the test temperature of 200°C, the emissivity of the infrared camera temperature sensor is adjusted, and when the emissivity is 0.95, the temperature measured by the infrared temperature sensor is the same as the temperature measured by the thermocouple, and the accurate emissivity of the adhered coating sample is obtained.

[0034] S4, installing the treated sample on an ultrasonic fatigue testing machine, setting up an infrared monitoring device, and inputting the coating emissivity measured in step S3 into the infrared detection device;

[0035] It is understandable that the infrared monitoring device is connected to a computer terminal, and a high frame rate mode is selected to record the video and image of the temperature field of the surface of the fatigue specimen to be tested changing with time during fatigue loading;

[0036] Preferably, the infrared monitoring device in step S4 is a high-speed and high-resolution infrared camera;

[0037] Furthermore, the lens of the infrared camera is aligned with the working section plane of the fatigue test sample, kept parallel to each other, and focused until the temperature field distribution on the surface of the fatigue test sample can be clearly observed;

[0038] Exemplarily, the sample is mounted on an ultrasonic fatigue testing machine, a high-resolution high-speed infrared camera is set up with its lens aimed at the working section of the sample, and a high-temperature resistant macro lens with a pixel resolution of 640×480 is installed, which is kept parallel to the plane of the working section at a distance of about 2 cm;

[0039] Focus the infrared camera or use automatic focus until the initial temperature field on the sample surface can be clearly monitored, and input the infrared emissivity of 0.95;

[0040] The infrared camera was connected to the computer, and the 30 frames / s high frame rate video mode was selected to record the video and image of the temperature field on the surface of the sample changing with time during the loading process.

[0041] S5. Set the stress ratio and stress amplitude, start the fatigue test, and simultaneously start the infrared monitoring device to record in real time to obtain a video file of infrared monitoring;

[0042] The infrared monitoring video file includes the temperature field formed by the local plastic deformation and heat dissipation of cracking of the processed sample, the temperature field change and the dynamic process of crack extension;

[0043] The dynamic process of crack extension is a dynamic process of crack extension observed by locating the crack tip through temperature field changes;

[0044] S6. Based on the video file of infrared monitoring, the length and time of the crack extension of the sample are obtained;

[0045] The length of the crack extension of the sample is characterized as the crack extension rate, which is expressed as:

[0046]

[0047] Among them, i / dt is the crack growth rate of the i-th frame, Δa i is the length of crack extension in the i-th frame, Δt is the unit time, a i is the crack length detected by infrared monitoring in the i-th frame.

[0048] According to the crack growth rate, the crack growth rate da based on the fatigue cycle number is obtained. i / dN is:

[0049]

[0050] Where N is the number of fatigue cycles, and f is the frequency of fatigue cycles;

[0051] The present invention further comprises step S7, according to which the crack growth rate da based on the fatigue cycle number is calculated. i / dN and stress intensity factor ΔK i , the relationship between crack growth rate and stress intensity factor is established.

[0052] The stress intensity factor ΔK i The expression is:

[0053]

[0054] Where C is the location parameter of the crack, σ a is the fatigue cycle stress.

[0055] Compared with the prior art, the present invention has at least the following beneficial effects:

[0056] (1) The present invention realizes visualization and in-situ monitoring of internal fatigue cracks that are difficult to detect in real time under ultra-long life conditions. It can not only accurately locate the initiation position of internal cracks, but also record the crack propagation process in detail. The acquired data is rich and accurate, and can detect small crack changes of several microns and temperature field changes at the initial stage of crack initiation;

[0057] (2) The monitoring device of the present invention has no contact with the fatigue specimen and has no impact on the fatigue test equipment. It is easy to install and debug, saving time and economic costs. It has fast response time and high-quality recording accuracy, and the output data is reliable;

[0058] (3) The method of the present invention has strong generalization ability and can be applied to crack growth rate testing of various materials under various fatigue conditions, not limited to ultrasonic fatigue and internal crack monitoring of the present invention. Surface crack monitoring, other types of specimens, and other fatigue test frequencies are also applicable to the method proposed by the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] The drawings are only for the purpose of illustrating particular embodiments and are not to be construed as limiting the invention.

[0060] Figure 1 It is a flow chart of the visualized ultra-high cycle fatigue internal crack growth rate disclosed in an embodiment of the present invention;

[0061] Figure 2 It is a schematic diagram of the ultrasonic fatigue specimen size and infrared monitoring area disclosed in an embodiment of the present invention;

[0062] Figure 3 It is a schematic diagram of a crack extension behavior result diagram of infrared monitoring disclosed in an embodiment of the present invention;

[0063] Figure 4 Schematic diagram of the relationship between crack growth rate and stress intensity factor disclosed in an embodiment of the present invention. DETAILED DESCRIPTION

[0064] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. In addition, the present invention can also be implemented in other ways different from those described herein, and therefore, the protection scope of the present invention is not limited by the specific embodiments disclosed below.

[0065] A specific embodiment of the present invention, as Figure 1-4 The present invention provides a method for determining the internal crack growth rate of ultra-high cycle fatigue by visualization. In order to illustrate the effectiveness of the method proposed by the present invention, the above technical solution of the present invention is described in detail through a specific embodiment below. The specific implementation steps are as follows:

[0066] S1. Processing a fatigue specimen to be tested; the fatigue specimen to be tested is a variable-section plate-shaped ultrasonic fatigue specimen;

[0067] Preferably, the shape and size of the fatigue specimen to be tested in step S1 are designed according to the dynamic elastic modulus and density of the fatigue specimen to be tested;

[0068] Exemplarily, the fatigue specimen to be tested is processed by an electric spark wire cutting machine.

[0069] The size of the variable cross-section plate-shaped ultrasonic fatigue specimen in step S1 of the present invention satisfies ultrasonic resonance and facilitates high-precision infrared monitoring of the initiated fatigue cracks;

[0070] Exemplarily, a Ti-6Al-4V alloy prepared by additive manufacturing is selected and placed in a heat treatment furnace for 2 hours at 600° C. to obtain a fatigue specimen to be tested;

[0071] The dynamic elastic modulus of the fatigue specimen to be tested is 96.455 GPa;

[0072] The density of the fatigue specimen to be tested is 4.38 g / cm 3 .

[0073] Exemplarily, the ultrasonic resonance frequency of the ultrasonic fatigue testing machine is 20 kHz;

[0074] S2, performing secondary grinding and coating deposition treatment on the surface of the fatigue specimen to be tested to obtain a treated specimen;

[0075] Preferably, the specific steps of obtaining the processed sample in step S2 include:

[0076] Performing mechanical grinding and electrolytic polishing on the surface of the fatigue specimen to be tested, and depositing a matte coating evenly on the surface of the fatigue specimen to be tested after the treatment, to obtain a treated specimen;

[0077] Furthermore, the infrared emissivity of the matte coating is 0.9 to 1;

[0078] Exemplarily, step S2 performs secondary grinding and coating deposition on the surface of the fatigue specimen to be tested, and the specific steps of obtaining the treated specimen include:

[0079] Step S21, using a CNC grinder to perform a first polishing on the surface of the fatigue specimen to be tested; the roughness of the CNC grinder is Ra<0.4;

[0080] Step S22, using 3000-mesh sandpaper and a diamond polishing agent with a particle size of 0.25 μm to perform a second polishing on the surface of the fatigue specimen to be tested after the first polishing;

[0081] Step S23, placing the fatigue specimen to be tested after the second polishing into an alcohol bath configured with polishing liquid;

[0082] It is understood that the temperature of the alcohol bath is -19--21°C;

[0083] The polishing liquid comprises 5.5±6.5% perchloric acid, 58.5-59.5% methanol and 34.5-35.5% n-butanol;

[0084] Step S24, after the temperature is constant at -19--21°C, connect the cleaned sample to the anode of a DC stabilized power supply, connect the cathode of the DC stabilized power supply to a copper sheet, place them together in a polishing liquid, and put a magnetic rotor that continuously stirs the polishing liquid;

[0085] Step S25, power on for 30 seconds to perform electrolytic polishing. After polishing, wash in pure alcohol and quickly dry to obtain a cleaned sample;

[0086] Step S26: using an atomizing device to deposit a layer of matte water-based paint on the surface of the cleaned sample to obtain a treated sample.

[0087] The complex phase interface formed by multiple resin components of the matte water-based paint in the present invention forms a slightly rough surface with strong diffuse reflection of light after the coating is cured, thereby increasing the emissivity of the sample surface and avoiding the reflection of infrared rays by metal, thereby affecting the monitoring quality.

[0088] S3. Before the fatigue test, the emissivity of the coating deposited on the surface of the treated sample is measured to obtain the coating emissivity;

[0089] Preferably, in step S3, a thermocouple and an infrared camera calibrated by a black body are used to measure the emissivity of the coating deposited on the surface of the treated sample to obtain the emissivity of the coating.

[0090] For example, the treated sample is placed in an induction coil, a k-type thermocouple is selected for temperature measurement, and the thermocouple is fixed on the surface of the sample using a spot welder under a welding current of 60A;

[0091] At the same time, a high-precision infrared camera calibrated by a black body is selected for synchronous temperature measurement.

[0092] Furthermore, when the temperature measured by the thermocouple reaches the test temperature of 200°C, the emissivity of the infrared camera temperature sensor is adjusted, and when the emissivity is 0.95, the temperature measured by the infrared temperature sensor is the same as the temperature measured by the thermocouple, and the accurate emissivity of the adhered coating sample is obtained.

[0093] S4, installing the treated sample on an ultrasonic fatigue testing machine, setting up an infrared monitoring device, and inputting the coating emissivity measured in step S3 into the infrared detection device;

[0094] It is understandable that the infrared monitoring device is connected to a computer terminal, and a high frame rate mode is selected to record the video and image of the temperature field of the surface of the fatigue specimen to be tested changing with time during fatigue loading;

[0095] Preferably, the infrared monitoring device in step S4 is a high-speed and high-resolution infrared camera;

[0096] Furthermore, the lens of the infrared camera is aligned with the working section plane of the fatigue test sample, kept parallel to each other, and focused until the temperature field distribution on the surface of the fatigue test sample can be clearly observed;

[0097] Exemplarily, the sample is mounted on an ultrasonic fatigue testing machine, a high-resolution high-speed infrared camera is set up with its lens aimed at the working section of the sample, and a high-temperature resistant macro lens with a pixel resolution of 640×480 is installed, which is kept parallel to the plane of the working section at a distance of about 2 cm;

[0098] Focus the infrared camera or use automatic focus until the initial temperature field on the sample surface can be clearly monitored, and input the infrared emissivity of 0.95;

[0099] The infrared camera was connected to the computer, and the 30 frames / s high frame rate video mode was selected to record the video and image of the temperature field on the surface of the sample changing with time during the loading process.

[0100] S5. Set the stress ratio and stress amplitude, start the fatigue test, and simultaneously start the infrared monitoring device to record in real time to obtain a video file of infrared monitoring;

[0101] The infrared monitoring video file includes the temperature field formed by the local plastic deformation and heat dissipation of cracking of the processed sample, the temperature field change and the dynamic process of crack extension;

[0102] The dynamic process of crack extension is a dynamic process of crack extension observed by locating the crack tip through temperature field changes;

[0103] For example, a sine wave load spectrum with a stress ratio of -1 and a stress amplitude of 325 MPa is set on the computer controlling the ultrasonic fatigue testing machine, and the fatigue test is started; at the same time, a high-speed infrared camera is turned on to synchronously record the heat dissipation temperature field formed by local deformation and cracking inside the material on the surface of the sample, and the dynamic process of crack extension is recorded by the change and movement of the temperature field representing the crack tip;

[0104] Figure 3 24 frames of images are shown showing the changes in temperature field with crack extension during ultrasonic fatigue of a sample with a stress amplitude of 325 MPa. The point where the peak temperature of the temperature field changes compared to the previous frame represents the plastic zone at the crack tip with the largest heat dissipation, and the movement of the peak temperature point represents the expansion of the crack.

[0105] S6. Based on the video file of infrared monitoring, the length and time of the crack extension of the sample are obtained;

[0106] The length of the crack extension of the sample is characterized as the crack extension rate, which is expressed as:

[0107]

[0108] Among them, i / dt is the crack growth rate of the i-th frame, Δa i is the length of crack extension in the i-th frame, Δt is the unit time, a i is the crack length detected by infrared monitoring in the i-th frame.

[0109] According to the crack growth rate, the crack growth rate da based on the fatigue cycle number is obtained. i / dN is:

[0110]

[0111] Where N is the number of fatigue cycles, and f is the frequency of fatigue cycles;

[0112] The present invention further comprises step S7, according to which the crack growth rate da based on the fatigue cycle number is calculated. i / dN and stress intensity factor ΔK i , the relationship between crack growth rate and stress intensity factor is established.

[0113] The stress intensity factor ΔK i The expression is:

[0114]

[0115] Where C is the location parameter of the crack, σ a is the fatigue cycle stress.

[0116] Table 1 Infrared monitoring and calculation results

[0117]

[0118] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A visual method for determining the internal crack growth rate of ultra-high cycle fatigue, characterized in that: include: S1. Processing a fatigue specimen to be tested; the fatigue specimen to be tested is a variable-section plate-shaped ultrasonic fatigue specimen; S2, performing secondary grinding and coating deposition treatment on the surface of the fatigue specimen to be tested to obtain a treated specimen; S3. Before the fatigue test, the emissivity of the coating deposited on the surface of the treated sample is measured to obtain the coating emissivity; S4, installing the treated sample on an ultrasonic fatigue testing machine, setting up an infrared monitoring device, and introducing the coating emissivity described in step S3 into the infrared detection device; S5. Set the stress ratio and stress amplitude, start the fatigue test, and simultaneously start the infrared monitoring device to record in real time to obtain a video file of infrared monitoring; The infrared monitoring video file includes the temperature field formed by the local plastic deformation and heat dissipation of cracking of the processed sample, the temperature field change and the dynamic process of crack extension; The dynamic process of crack extension is a dynamic process of crack extension observed by locating the crack tip through temperature field changes; S6. Based on the infrared monitoring video file, the length and time of the crack extension of the treated sample are obtained; Characterizing the length of crack extension of the sample as crack extension rate; According to the crack growth rate, the crack growth rate based on the fatigue cycle number is obtained.

2. A visual method for determining the internal crack growth rate of ultra-high cycle fatigue according to claim 1, characterized in that: The size of the variable cross-section plate-shaped ultrasonic fatigue specimen in step S1 satisfies ultrasonic resonance.

3. The method for determining the visual ultra-high cycle fatigue internal crack growth rate according to claim 1, characterized in that: The specific steps of obtaining the processed sample in step S2 include: The fatigue specimen to be tested is subjected to surface mechanical grinding and electrolytic polishing treatment, and a matte coating is evenly deposited on the surface of the fatigue specimen to be tested after the treatment to obtain a treated specimen.

4. A method for determining the visual ultra-high cycle fatigue internal crack growth rate according to claim 3, characterized in that: The infrared emissivity of the matte coating is 0.9-1.

5. The method for determining the visual ultra-high cycle fatigue internal crack growth rate according to claim 1, characterized in that: Step S2 performs secondary grinding and coating deposition on the surface of the fatigue specimen to be tested, and the specific steps of obtaining the treated specimen include: Step S21, using a CNC grinder to perform a first polishing on the surface of the fatigue specimen to be tested; Step S22, using sandpaper and diamond polishing agent to perform a second polishing on the surface of the fatigue specimen to be tested after the first polishing; Step S23, placing the fatigue specimen to be tested after the second polishing into an alcohol bath configured with polishing liquid; Step S24, after the temperature is constant, connect the cleaned sample to the anode of a DC stabilized power supply, connect the copper sheet to the cathode of the DC stabilized power supply, place them together in a polishing liquid, and put a magnetic rotor that continuously stirs the polishing liquid; Step S25, power on for electrolytic polishing, after polishing, clean in pure alcohol and quickly dry to obtain a cleaned sample; Step S26: deposit a layer of matte water-based paint on the surface of the cleaned sample to obtain a treated sample.

6. A visual method for determining the internal crack growth rate of ultra-high cycle fatigue according to claim 1, characterized in that: In step S3, a thermocouple and an infrared camera calibrated by a black body are used to measure the emissivity of the coating deposited on the surface of the treated sample to obtain the emissivity of the coating.

7. A visual method for determining the internal crack growth rate of ultra-high cycle fatigue according to claim 1, characterized in that: The infrared monitoring video file includes the temperature field formed by local plastic deformation and heat dissipation of cracking of the processed sample, the temperature field change and the dynamic process of crack extension.

8. The method for determining the visual ultra-high cycle fatigue internal crack growth rate according to claim 1, characterized in that: The dynamic process of crack extension is a dynamic process of crack extension observed by locating the crack tip based on the change of temperature field.

9. The method for determining the visual ultra-high cycle fatigue internal crack growth rate according to claim 1, characterized in that: The expression of the crack growth rate based on the fatigue cycle number is: Among them, i / dN is the crack growth rate based on the fatigue cycle number, da i is the crack length detected by infrared monitoring in the i-th frame, N is the number of fatigue cycles, and f is the frequency of fatigue cycles; Δa i is the length of crack extension in the i-th frame, and Δt is the unit time.

10. The method for determining the visual ultra-high cycle fatigue internal crack growth rate according to claim 1, characterized in that: The method further comprises step S7, establishing a relationship between the crack growth rate and the stress intensity factor based on the crack growth rate and the stress intensity factor based on the fatigue cycle number.

Citation Information

Patent Citations

  • System for predicting fatigue limit of magnesium alloy member based on infrared thermal imaging, and method thereof

    CN103076243A

  • Fatigue crack growth rate measurement method based on infrared thermal imaging technology

    CN108760546A

  • Ultrasonic fatigue crack propagation rate measurement method based on inherent frequency

    CN111678990A

  • High-efficiency in-situ ultrasonic fatigue experiment system based on heat dissipation and implementation method thereof

    CN112666013A

  • Infrared detection method for initial damage transition of wind power blade girder

    CN116680877A

Cited By

  • High-cycle fatigue crack identification method based on temperature change

    CN121577622A

  • High-cycle fatigue crack identification method based on temperature change

    CN121577622B